Nurse-led secondary preventive follow-up after stroke/TIA and ACS for patients aged 80 years or older: A post-hoc analysis of the randomized controlled NAILED trial - Karl Ingard; Anna-Lotta Irewall; Thomas Mooe; Joachim Ögren (PLoS ONE, 2025)
Background The evidence supporting secondary prevention with antihypertensives and lipid-lowering drugs after cerebrovascular disease or acute coronary syndrome (ACS) is not as strong for persons aged ≥80 years. The Nurse-based, Age-independent Intervention to Limit Evolution of Disease (NAILED) trial was a randomized controlled trial in which secondary preventive follow-up with titration of antihypertensives and lipid-lowering drugs was compared to usual care. In this substudy, we investigated the efficacy and safety of the NAILED intervention in persons aged ≥80 years. Methods and findings Patients admitted to Östersund Hospital with ACS, stroke, or transient ischemic attack between 2010 and 2014 were randomized to a nurse-led telephone-based follow-up (intervention group) or usual care (control group) and followed from discharge until 31 December 2017, with a maximum follow-up of 5 years. This post-hoc analysis included all patients aged ≥80 years (n = 394). The primary outcome was a composite of cardiovascular death, myocardial infarction, and stroke. The secondary endpoints were cardiovascular death, myocardial infarction, stroke, ischemic stroke, all-cause mortality, fracture, orthostatic hypotension, serious bleeding, and health-related quality of life. During a mean follow-up of 3.8 years, 31.7% (n = 64) of the patients in the intervention group and 37.5% (n = 72) in the control group reached the primary endpoint (HR 0.82, 95% CI 0.58–1.14, P = 0.23). The risk of cardiovascular death was significantly decreased (HR 0.64, 95% CI 0.41–0.998, P = 0.049) and the risk of fracture non-significantly increased (HR 1.47, 95% CI 0.95–2.27, P = 0.08) in the intervention group compared to the control group. Conclusions The intervention in the NAILED trial did not reduce the risk of major cardiovascular events in patients aged ≥80 years. The trends of lower risk of cardiovascular events and increased risk of fractures need to be validated in future research. Trial registration ISRCTN23868518, ISRCTN96595458. The NAILED risk factor trial is registered in the ISRCTN registry, (ISRCTN23868518) for the stroke/TIA and (ISRCTN96595458) for the ACS cohort. The strict ICMJE requirement of prospective registration of clinical trials came to our attention when the recruitment had already begun. The study was therefore retrospectively registered on 19 June 2012. We confirm that all related and ongoing trials are now registered.